Pengaruh Motivasi Belajar Terhadap Prestasi Siswa di Sekolah - Ayudia Nur Annisa (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2019)
This study aims to find out how the influence of learning motivation on student achievement in school. This research is focused on the teacher's role in fostering student learning motivation. This motivation is very important for improving student learning achievement. Because as is well known, student motivation in learning is lacking. This will affect its success in learning. For this reason, there is a need for efforts by teachers to increase interest in learning and motivate students to be more enthusiastic about achieving in school. The approach taken in this journal research is the approach (library research) which uses literature as its object. From the research of several literatures, the results of this study indicate that learning motivation has an influence on student learning activities, especially on student achievement. The higher the student's motivation, the better the learning achievement. Vice versa, the lower the motivation of student learning, it will be difficult for these students to achieve achievement in learning. The teacher also has a very important role and has an influence on student motivation in school.